Modeling energy and mass balance of Shallap Glacier, Peru - Gurgiser, Wolfgang (2013)
Original abstract: We calculated the distributed surface mass and energy balance of Shallap Glacier, Cordillera Blanca, Peru (9° S, 77° W, 4700–5700 m a.s.l., ~ 7 km2), on hourly time steps for two years (September 2006–August 2008) using a process-based model and meteorological measurements as input. Model parameter combinations were optimized against 21 temporal readings of 20 stakes in the ablation zone of the glacier. Uncertainty caused by model input parameters and parameterization schemes was estimated using a leave-one out cross-validation scheme, which yields values of root mean square deviation (RMSD) of surface height change < 1 m (< 10% of the measured amplitude) for all stakes. With the best parameter combination (smallest RMSD) applied, the modeled annual surface mass balance of the glacier was -0.32 ± 0.4 m w.e. (water equivalent) for September 2006–August 2007 and 0.51 ± 0.56 m w.e. for September 2007–August 2008. While the mass balance above 5000 m was similar in both years (¿ 0.33 ± 0.68 m w.e.) due to similar annual sums of solid precipitation, a difference of 1.97 ± 0.68 m w.e. was calculated for the lower parts of the glacier. This difference is associated with more frequent occurrence of higher snow line altitudes during the first year, which was mainly caused by a higher fraction of liquid precipitation due to higher mean air temperatures. As the net shortwave budget was found to be the main source for ablation throughout the year at Shallap Glacier, lower surface albedo especially caused by lower solid precipitation amounts explains most of the difference in modeled ablation and mass balance between the two years.